Temporal Trends in Predictors of Early and Late Mortality After Emergency Coronary Artery Bypass Grafting for Cardiogenic Shock Complicating Acute Myocardial Infarction. Issue 17 (25th October 2016) - Davierwala, Piroze M.; Leontyev, Sergey; Verevkin, Alexander; Rastan, Ardawan J.; Mohr, Matthias; Bakhtiary, Farhad; Misfeld, Martin; Mohr, Friedrich W.
Abstract : Background: Cardiogenic shock after acute myocardial infarction is an indication for emergent coronary artery bypass grafting in patients not amenable to percutaneous coronary intervention. Our study aimed to evaluate and identify risk factors for early and long-term outcomes in such patients. Methods: A total of 508 patients who underwent coronary artery bypass grafting for cardiogenic shock complicating acute myocardial infarction between January 2000 and June 2014 were divided into 3 time cohorts: 2000 to 2004 (n=204), 2005 to 2009 (n=166), and 2010 to 2014 (n=138). Predictors of in-hospital mortality for each time cohort and long-term mortality for all patients were identified by logistic and Cox regression analyses, respectively. Results: Mean age was 68.3±9.8 years. Of the 508 patients, 78.5% had 3-vessel and 47.1% had left main disease. Left ventricular function <30% was observed in 44.1% of patients, with 30.4%, 37.9%, 52.9%, and 3.1% requiring preoperative resuscitation, ventilation, intra-aortic balloon pump, and extracorporeal membrane oxygenation support, respectively. Overall in-hospital mortality was 33.7%; declined from 42.2% to 30.7% to 24.6%, respectively, for the 3 time cohorts ( P =0.02); and was independently predicted by serum lactate >4 mmol/L (odds ratio [OR], 4.78; 95% confidence interval, 2.88–7.95; P <0.0001), ST-segment–elevation myocardial infarction (OR, 2.10; 95% confidence interval, 1.36–3.26; P =0.001), age >75 years (OR, 2.01; 95% confidence interval, 1.06–3.85; P =0.03), and left ventricular ejection fraction <30% (OR, 1.83; 95% confidence interval, 1.15–2.91; P =0.01). Cumulative survival was 42.6±2.0% and 33.4±2.0% at 5 and 10 years, respectively, and correspondingly improved to 64.3±3.0% and 49.8±3.0% in hospital survivors. Serum lactate >4 mmol/L (OR, 2.2; P <0.0001), incremental age (OR, 1.05; P <0.0001), New York Heart Association class IV (OR, 1.33; P =0.02), diabetes mellitus (OR, 1.39; P =0.005), and preoperative inotropic (OR, 2.61; P =0.001) and extracorporeal membrane oxygenation (OR, 1.68; P =0.05) support predicted late mortality. Conclusions: Emergency coronary artery bypass grafting in patients with acute myocardial infarction complicated by cardiogenic shock is associated with a high in-hospital mortality, which showed a significant decline with time. Hospital survivors have good long-term outcomes, which demonstrate the beneficial effect of surgical revascularization. Preoperative serum lactate >4 mmol/L is a strong predictor of both early and late mortality. Abstract : Supplemental Digital Content is available in the text.